Discussion of Relationship between Accounting Changes and Stock Prices: Problems of Measurement and Some Empirical Evidence - Demski, Joel S. (Journal of Accounting Research, 1973)
Joel S. Demski, Discussion of Relationship between Accounting Changes and Stock Prices: Problems of Measurement and Some Empirical Evidence, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 46-54